Exploring Students’ Learning Motivation and Speaking Confidence Through Edutainment A Case Study on Clash of Champions at UIN Palangka Raya - Musdalifah, Mayra; Qalyubi, Imam; Qamariah, Zaitun (Jurnal Pendidikan Indonesia, 2025)
The purpose of this study was to explore how Clash of Champions, an edutainment-based learning competition program, influenced students’ learning motivation and speaking confidence among English Education students at UIN Palangka Raya. The study focused on passive viewers who watched the program outside classroom settings. This research employed a qualitative case study design. The data were collected through semi-structured interviews, observations, and focus group discussions (FGD) involving selected undergraduate students. The data were analyzed using thematic analysis to identify emerging themes related to learning motivation and speaking confidence. The findings revealed that Clash of Champions positively affected students’ learning motivation by fostering autonomy, competence, relatedness, and emotional engagement. Students were intrinsically motivated because they enjoyed the show and felt inspired by the contestants’ performances. Extrinsically, they were motivated by the desire to improve their English skills for future goals. Regarding speaking confidence, students reported feeling more confident and less anxious about speaking in English after observing the fluent performance of participants in the program. The study indicates that Clash of Champions provided students with vicarious learning experiences that strengthened their self-efficacy and willingness to communicate. In conclusion, Clash of Champions as an edutainment program effectively enhanced both motivation and confidence in learning English. It provided authentic and engaging exposure to language use while promoting positive emotional responses. The study suggests that integrating edutainment media into English teaching can support affective and communicative learning outcomes.